Effect of Chip Breaker Geometries on Cutting Force A Finite Element Analysis - Fawzi Zamria, Mohd; Nor Sufyan Sudin, Mohd; Nur Rosyidi, Cucuk; Bin Yusoff, Ahmad Razlan (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2025)
Continuous chip formation during metal cutting operations poses substantial challenges, from deteriorating surface finish to accelerated tool wear. Our research examines how six chip breaker geometric parameters of insert rake angle, land, radius, width, height, and nose radius influence cutting forces in turning operations. Using DEFORM-3D, we simulated 27 distinct chip breaker configurations based on Taguchi's L27 orthogonal array while maintaining constant cutting parameters of 275 mm/min speed, 0.2 mm/rev feed, and 1.0 mm depth. ANOVA findings showed that nose radius was most influential with F-ratio equal to 27.41, followed by insert width and rake angle. The optimized geometry of the rake angle is 16°, the land is 0.1 mm, the radius is 0.5 mm, width is 2.0 mm, height is 0.25 mm, and the nose radius is 0.8 mm achieved the lowest cutting force of 798 N, a 15.8% reduction from the experimental average. This research replaces traditional trial-and-error approaches with systematic optimization, providing manufacturers with specific guidelines for enhancing chip control, surface quality, and tool life in industrial applications.